2002
DOI: 10.1063/1.1486482
|View full text |Cite
|
Sign up to set email alerts
|

On-chain defect emission in electroluminescent polyfluorenes

Abstract: We present time-resolved photoluminescence measurements on a range of poly- and oligofluorenes with different molecular weights in both dilute solution and thin films. The commonly observed parasitic broad green emission band, which has previously been attributed to an excimer, is identified in all solution and film samples and assigned to an on-chain emissive defect. By comparison of the luminescence decay in the solid state at different temperatures it is shown that, at room temperature, intramolecular relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
149
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(157 citation statements)
references
References 16 publications
7
149
0
1
Order By: Relevance
“…The presence of keto type defects is thought to be low in this sample because its characteristic emission 40 F-C type features appear to be superimposed on an extremely broad emission "band" which is centered near 2.4 eV. This underlying background originates from a variety of potential experimental sources including residual α phase emission, unresolved vibronic replicas and interchain (IC) excitations 40,42 in addition to the chemical defects just discussed. The background profile can also be model dependent 43 .…”
Section: Resultsmentioning
confidence: 99%
“…The presence of keto type defects is thought to be low in this sample because its characteristic emission 40 F-C type features appear to be superimposed on an extremely broad emission "band" which is centered near 2.4 eV. This underlying background originates from a variety of potential experimental sources including residual α phase emission, unresolved vibronic replicas and interchain (IC) excitations 40,42 in addition to the chemical defects just discussed. The background profile can also be model dependent 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Later, however, it has been shown that emission in the green spectral range originates from a keto defect formed as a result of photooxidation or thermal oxidation [16][17][18][19][20][21][22] . Copolymers and oligomers containing well-defined fractions of fluorenone as a model of the oxidized species showed emission from the fluorenone unit that is photophysically identical to the green band in polyfluorene 23 .…”
mentioning
confidence: 99%
“…The origin of these emission features has been the subject of hot discussion. Fourier transform infrared (FTIR) spectroscopy has revealed that fluorenone defects, formed on degradation of PFs, are related to the intensity of the low-energy emission band (15,19,(31)(32)(33)(34)(35)(36)(37)(38). The idea that fluorenones could be responsible for the green light emission was substantiated by the synthesis of poly-and oligofluorenes containing a precise number of fluorenone moieties that exhibit green emission, even in dilute solution (24,33,(39)(40)(41).…”
Section: Resultsmentioning
confidence: 98%